1982
DOI: 10.1126/science.215.4540.1629
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Blooms: Carbon and Nitrogen Limitation Have Opposite Effects on the Buoyancy of Oscillatoria

Abstract: Gas vacuolation in Oscillatoria rubescens decreased with increased nitrogen limitation and increased with transitions from nitrogen to inorganic carbon limitation. Gas vacuoles consist of protein vesicles that can accumulate in carbon- limited but not in unenriched nitrogen-limited cells. Nitrogen limitation is a factor in the formation of deep population maxima; carbon limitation can promote surface blooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…Direct evidence has come from the cyclostat experiments of Klemer et al (1982) who found increased gas vacuolation in Oscillatoria under C limitation. Walsby & Booker (1976) found less surface accumulation of A. flos-aquae in the half of a partitioned laboratory-column treated with carbonate while Paerl & Ustach (1982) found that the buoyancy of Aphanizomenon flos-aquae was highest under CO2-limiting conditions.…”
Section: Interactions Of Buoyancy Regulation Wit Limitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct evidence has come from the cyclostat experiments of Klemer et al (1982) who found increased gas vacuolation in Oscillatoria under C limitation. Walsby & Booker (1976) found less surface accumulation of A. flos-aquae in the half of a partitioned laboratory-column treated with carbonate while Paerl & Ustach (1982) found that the buoyancy of Aphanizomenon flos-aquae was highest under CO2-limiting conditions.…”
Section: Interactions Of Buoyancy Regulation Wit Limitationmentioning
confidence: 99%
“…Moreover, if additional supplies of limiting nutrients are made available to stratified populations, Oscillatoria spp. will move up to a new position in the light gradient where a new balance between carbon fixation rates and nutrient availability may be struck (Klemer 1976(Klemer , 1978Klemer et al 1982). Presumably, this upward migration could depend, in part, upon renewed gas-vesicle synthesis.…”
Section: Buoyancy Regulation In Gas-vacuolate Cyanobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Specific physiologic capabilities of cyanobacteria enable them to compete very efficiently with other photosynthetic microorganisms. Most cyanobacterial species regulate their buoyancy (by means of gas-vacuoles) and this allows them to colonize different depths in the water column depending on the localization of nutrients and the availability of light [63,122]. Possession of accessory pigments, such as phycoerythrin, allows several species to carry out photosynthesis at depths that receive only green light and where, in addition, nutrients are more abundant than on the surface (surface waters are rapidly depleted following spring algal proliferations).…”
Section: Biology and Ecologymentioning
confidence: 99%
“…The average C : N : P ratio by weight of the seston in these lakes was 130 : 13 : 1 while ratios of unfertilised lakes were slightly less (118: 11 : 1, Schindler 1971). Carbon may nevertheless influence the relative proportion of cyanobacteria (Shapiro 1973), scum formation (Paerl & Ustach 1982), and migration behaviour (Klemer et al 1982) -particularly in low-alkalinity waters. In a series of enclosure experiments in Lake Emily, Minnesota, Shapiro (1973) found that the addition of CO 2 and nutrients N and P at a supply ratio of 7 shifted the community dominance to chlorophytes.…”
Section: Carbon and Cyanobacteriamentioning
confidence: 99%